2012
DOI: 10.1179/1743294411y.0000000035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surfactants on performance of electroless plating baths for nickel–ceramic composite membrane fabrication

Abstract: Nickel-ceramic microfiltration membranes were prepared by electroless deposition of nickel on the activated ceramic membrane substrates having a nominal pore size of 275 nm. Two different surfactants, namely sodium dodecyl sulphate (SDS) and cetyltrimethyl ammonium bromide (CTAB), were studied for their ability to alter the performance characteristics of plating baths as well as composite membranes. Parameters evaluated include the bath conversion, plating efficiency, metal film thickness, average pore size of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
(34 reference statements)
1
15
0
Order By: Relevance
“…The obtained results indicated that the positive effect of the surfactant on deposit properties was improved with pH of the coating bath. The results suggest that addition of the surfactant caused a greater adsorption of Ni 2+ and consequently higher deposition rates, effects that were also described by Chen et al 32 and Kumor 25 . In addition, Chen et al 32 found that addition of low concentrations of surfactants to the electroless solution caused higher deposition rates (up to 26% greater than the deposition rate from a surfactant-free bath).…”
Section: It Seems That Sds Improves Formation Of En-p Coating By Prom...supporting
confidence: 80%
“…The obtained results indicated that the positive effect of the surfactant on deposit properties was improved with pH of the coating bath. The results suggest that addition of the surfactant caused a greater adsorption of Ni 2+ and consequently higher deposition rates, effects that were also described by Chen et al 32 and Kumor 25 . In addition, Chen et al 32 found that addition of low concentrations of surfactants to the electroless solution caused higher deposition rates (up to 26% greater than the deposition rate from a surfactant-free bath).…”
Section: It Seems That Sds Improves Formation Of En-p Coating By Prom...supporting
confidence: 80%
“…The co-deposition process in electroless composite coatings has been correlated to Langmuir physical adsorption and Temkin chemical adsorption by Balaraju et al 18 Surfactants can also modify the surface electric charge of the particles and subsequently, the homogeneous dispersion of particles without any agglomeration in the coating. 19,20 CTAB as a cationic surfactant could adjust the surface electric charge and uniform distribution of silver particles in the plating bath. Spot EDS analysis of Ni-P matrix showed high phosphorous content in Ni-P based coating (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…micellar-enhanced microfiltration of heavy metal ions and treatment of industrial effluents [10][11][12][13][14][15]. In addition, they are used as supports for preparing composite membranes such as polymer/ceramic ultrafiltration membranes and metal/ceramic composite membranes [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%